Volunteersâ€™ Employment and Counterinsurgency in Italy: The Case the Hungarian Legion (1861-1862) - Carteny, Andrea (Mediterranean Journal of Social Sciences, 2012)
In South-Italy the brigandage is a complex phenomenon, deeply popular and culturally reactionary: a â€œgreatbrigandageâ€ emerged in dangerous and structural forms after the fall of the last Bourbon king and the Italian unification under theSavoy dynasty, in 1861. From the â€œMilleâ€ expedition and the conquest of redshirts leaded by Garibaldi, the Southern Army andthe Italian Army fought against the brigandage as a real insurgency movement supported by Bourbonsâ€™ loyalists and Catholicenvironments. In the campaign of banditismâ€™s repression a particular case was the employment of volunteers, as the formerGaribaldiâ€™s Hungarian Legion. From the General Staff Armyâ€™s Historical Archive the documents show both Commandâ€™s strategyand local tactics in the Hungarian practices. The concentration of the legionaries in Nocera (March 1861) and the growingnumber of effectives in few months (less than 1 thousand) gave the opportunity of their employment for more than 1 year in alarge area of Southern regions. The Hungarian legionariesâ€™ mutiny, in July 1862, rised at the same time of the Garibaldiâ€™sexpedition from South to Rome, blocked in August at the Aspromonte. After the disarm of the soldiers, the calling back to Torinomeant the risk of his dissolution. Only a complete reorganization, in 1863, allowed to employ back a new Legion until 1867.